The crack propagation and dynamic impact responses of tempered laminated glass used in high-speed trains. (April 2022) - Wang, Shiming; Peng, Yong; Chen, Xuanzhen; Wang, Kui
Highlights: Proposed a method to simulate the residual stress in tempered glass. Developed a simulation framework for tempered laminated glass. Characterized the typical crack features and propagation process of tempered laminated glass. Formulated the relationships between geometrical variables and impact mechanical responses. Abstract: The tempered laminated windshield used in high speed train is different with that used in auto. This work aims to study the crack propagation and dynamic impact responses of tempered laminated windshield. To achieve this point, a cohesive element based finite element model that take residual stress into consideration was built and validated by safety hammer impact experiment. Afterwards, the crack features and propagation process were characterized. The simulation results show that the fracture fronts in the interior tensile zone is ahead of that in the near surface compression zone and the fragment is much smaller than that of float glass, which demonstrate residual stress has significant influence on fracture mechanism and crack modes. And then, a parametric discussion about the influence of impact velocity and thickness of tempered laminated glass's components on the impact performances were carried out and correlated. The results show that the impact responses are velocity sensitivity. The front glass layer (G1) has more significant effects on the energy absorption and peak acceleration comparing with back glass layer (G2). In practical engineering application, increasing the thickness of PVB film appropriately could not only reduce peak acceleration but also consume more impact kinetic energy.